Expression of the Saccharomyces cerevisiae GAL7 gene on autonomous plasmids. - Baker, S M (1984)
We used a combination of cloned DNA fragments encoding the GAL7 gene, yeast plasmid vectors, and chromosomal gal7 deletions to characterize the in vivo transcription of the GAL7 gene on autonomously replicating plasmids. Our results demonstrated that a plasmid-borne 3.1-kilobase DNA fragment containing the GAL7 gene provides sufficient information to mimic the regulated expression of the chromosomal location. Normal expression of GAL7 could occur in the absence of DNA encoding the functional genes of the GAL cluster region and was not altered when the gene was adjacent to other plasmid elements such as autonomously replicating sequences or centromeres. The chromosomal and single-copy centromeric plasmid locations of GAL7 were indistinguishable in their response to growth conditions (induction by galactose, repression by glucose) and positive and negative regulatory factors (GAL4 and GAL80). Increasing the gene dosage to more than 200 copies per cell resulted in constitutive expression of the GAL7 mRNA; fully induced mRNA levels were increased more than 10-fold at these high gene dosages. When cells were shifted from noninducing to inducing conditions, the initial time of appearance and the rate of accumulation of GAL7 mRNA were altered in cell populations containing multiple GAL7 genes. The induction kinetics and final accumulation of the chromosomal GAL10 mRNA were also affected by the presence of multiple copies of the GAL7 gene; these results are consistent with a model involving limiting amounts of regulatory factors.